Implementing 3D Printing for the Long-Term Release of Biomacromolecules - Plender, Kristian (2023)
The advancement of new biotherapeutics demands appropriate strategies that allow effective delivery to the body for the treatment of chronic diseases, which is of growing importance globally. This includes the development of implantable delivery systems with enhanced control over release at an intended site with the desired dosing. Additive manufacturing (AM), often referred to as three-dimensional (3D) printing, has been identified due to the potential advantages. This includes lower-cost initial formulation trials, geometric control and spatial location of bioactives to better modulate delivery in comparison to common manufacturing routes e.g. tabletting.